Online Auction System for Guma Stocks - Tusingwire, Roseline; Ayebare, Nice (Kabale University, 2025)
This project Report outlines the development of an Online Auction System tailored for Guma stocks, aimed at enhancing online trading activities. The proposed system provides a centralized platform for the public to engage in efficient and transparent buying and selling of goods. The system's objectives include streamlining the online trading process, fostering a sense of community engagement, and providing a user-friendly platform for secure transactions. It incorporates features such as user authentication, product listings, real-time bidding. The system's architecture is designed to accommodate scalability and future enhancements. The research component of this project involves investigating current online trading methods, identifying challenges, and proposing solutions through the implementation of the Online Auction System. The study aims to involve key stakeholders, including the public and consumers, to ensure the system aligns with the diverse needs of the community. The anticipated outcomes of this project include improved efficiency in online trading, increased user satisfaction, and a valuable contribution to the's technological ecosystem. The successful implementation of The Online Auction System is expected to create a more vibrant and accessible marketplace within Guma stocks.